Lipschütz Genital Ulceration as Initial Manifestation of Primary Sjögren’s Syndrome - Filipa de Castro Coelho; Maria Amaral; Lúcia Correia; Maria João Nunes Campos; Tereza Paula; Augusta Borges; Jorge Borrego (Case Reports in Obstetrics and Gynecology)
Genital ulcers are challenging to any clinician and causes transcend many specialties. Skin ulceration in patients with primary Sjögren’s syndrome is infrequent but an established feature of cutaneous involvement. Although gynecological symptoms, such as vulvovaginal dryness, dyspareunia, and pruritus, are common in women with primary Sjögren’s syndrome, patients affected by vulvar ulcers are unknown. We describe an exceptional case of necrotic aphthous-type vulvar ulceration as initial presentation of primary Sjögren’s syndrome that was possibly triggered by an infectious agent. Successful healing was achieved with oral corticosteroids, despite some loss of labia minora and labia majora as sequelae of the necrotizing process. Reactive acute genital ulcers (Lipschütz ulcers) should be considered as a possible manifestation of many autoimmune/inflammatory disorders, beyond the classic associations such as Behçet’s syndrome or Crohn’s disease.